Association of C- Reactive Protein and HbA1c in the Severity of Coronary Artery Disease in Patients with Ischemic Heart Disease - Ahmed, Mohsin; Islam, Md Mesbahul; Rahman, Mohammad Arifur; Rubaiyat, Khandaker Abu; Khuda, CM Khudrate E; Ferdous, Kazi Abul Fazal; Das, Bikash Chandra; Hasan, Mahmudul; Majumder, Mizanur Rahman (Cardiovascular Journal, 2018)
Background: C-reactive protein (CRP) and glycohemoglobin (HbA1c) are established risk factors for the development of cardiovascular disease. We investigated the joint effects of these parameters on the severity of coronary artery disease (CAD) in patients with ischemic heart disease. Methods: This cross sectional study was performed on 668 patients of ischemic heart disease. CRP value were divided into normal (<6 mg/L), borderline (6-10 mg/L) and high (>10 mg/L) and HbA1c was divided <6.5% and ≥ 6.5%. After performing Coronary angiography the extent of disease was divided into insignificant CAD of (<50% stenosis), significant CAD considered as >50% stenosis and single vessel, double vessel, triple vessel CAD and normal coronaries. Results: Most (65.0%) of the patients belonged to age 41-60 years. The mean age was found 51.4±10.7 years. Majority (82.3%) of patients were male. Among risk factors, highest (40.0%) patients had hypertension followed by 209 (31.3%) diabetes mellitus and 204 (30.5%) smoker. The relationship of CRP with the whole spectrum of ischemic heart disease was found statistically significant (p<0.05). The relationship of HbA1c and CRP were significantly associated with the severity of coronary artery disease. At HbA1c e”6.5 percent, severe CAD (double vessel and triple vessel) were found higher in high CRP than normal and borderline CRP group. Conclusion: Inflammation, presented by CRP, and hyperglycemia, presented by HbA1c, jointly contributes to the cardiovascular risk of patients. Patients with high CRP and elevated HbA1c are associated with severe coronary artery diseases. Cardiovasc. j. 2018; 11(1): 53-58